Analisis Yuridis Kebijakan Hukuman Pidana Mengenai Tindakan Match Fixing Di Indonesia (International Forum of Researchers and Lecturers, 2024)
Football matches are one of the most popular sports matches in Indonesia. Victories between leagues are often awaited with great enthusiasm by some sports fans. However, in practice, there are incidents that are carried out by individuals to achieve certain goals in a match while fixing the future score. Match Fixing or match fixing is during a match to gain financial or sporting advantage. This action is indirectly an act of bribery which can be subject to the crime of bribery in accordance with Law Number 11 of 1980 concerning Bribery